Diversity of the reaction mechanisms of SAM-dependent enzymes - Qiu Sun; Mengyuan Huang; Yuquan Wei (Elsevier, 2021)
S-adenosylmethionine (SAM) is ubiquitous in living organisms and is of great significance in metabolism as a cofactor of various enzymes. Methyltransferases (MTases), a major group of SAM-dependent enzymes, catalyze methyl transfer from SAM to C, O, N, and S atoms in small-molecule secondary metabolites and macromolecules, including proteins and nucleic acids. MTases have long been a hot topic in biomedical research because of their crucial role in epigenetic regulation of macromolecules and biosynthesis of natural products with prolific pharmacological moieties. However, another group of SAM-dependent enzymes, sharing similar core domains with MTases, can catalyze nonmethylation reactions and have multiple functions. Herein, we mainly describe the nonmethylation reactions of SAM-dependent enzymes in biosynthesis. First, we compare the structural and mechanistic similarities and distinctions between SAM-dependent MTases and the non-methylating SAM-dependent enzymes. Second, we summarize the reactions catalyzed by these enzymes and explore the mechanisms. Finally, we discuss the structural conservation and catalytical diversity of class I-like non-methylating SAM-dependent enzymes and propose a possibility in enzymes evolution, suggesting future perspectives for enzyme-mediated chemistry and biotechnology, which will help the development of new methods for drug synthesis.